Challenges of Charity Hospitals in Tehran: Evidence of Private Sector Participation in the Provision of Health Care - Ebrahim Jaafaripooyan; Esmaeel Javadi Ghale; Mohamad Arab; Tahere Sharifi (Kerman University of Medical Sciences, 2018)
Background & Objectives: Charity hospitals with increasing public participation in the provision of health services could play an important role in assisting government for providing health care and promoting society health. Since most deprived people use the services of these hospitals, paying attention to these organizations and their management can help improve the quality and equality of health services distribution. Thus, this study aimed to explore the challenges of management of charity hospitals in Tehran province and provide solutions for these challenges in 2017. Methods: This qualitative phenomenological study was conducted in 2017. Data were collected through semi-structure interviews with 26 participants from various organizations including top and middle hospital managers, experts from Vice-chancellor in treatment affairs of Universities of Medical Sciences in Tehran, and the Endowments and Charity Affairs Organizations. Snowball sampling method was used to select the respondents. Data were analyzed using a thematic analysis method. Results: The challenges of charity hospitals could be categorized into 5 main codes including financial resources, human resources, physical and structural resources, management, and cultural challenges, and 13 sub codes. Conclusion: Endowment selling and creating endowment funds in charity hospitals to develop sustainable financial resources, supervision of Ministry of Health (MOH) and Universities of Medical Sciences (UMS) for teaching, quality improvement, development of human resources, reconciliation with the goals of the health system, participation in macro policy making and planning, development of structural standards for the management of these hospitals and their announcement by the MOH, are the main solutions for these challenges. Keywords: Charity hospitals, Qualitative study, Challenges, Tehran Citation: Jaafaripooyan E, Javadi Ghale E, Arab M, Sharifi T. Challenges of Charity Hospitals in Tehran: Evidence of Private Sector Participation in the Provision of Health Care. Journal of Health Based Research 2018; 3(4): 323-37.